MODIFIED FREE-VOLUME MODEL FOR PERVAPORATION OF WATER/ETHANOL MIXTURES THROUGH MEMBRANES CONTAINING HYDROPHILIC GROUPS OR IONS - KIM, HJ; JO, WH; KANG, YS (JOHN WILEY & SONS INC, 1995)
The free-volume model for pervaporation has been modified by considering the polar path, in order to apply the model to membranes containing hydrophilic groups. The free-volume parameters were determined by inverse gas chromatography. For the polyacrylonitrile (PAN) membrane, the transport mechanism could be analyzed only by the free-volume model; however, for a membrane containing a hydrophilic moiety, the transport properties could be interpreted by the modified model. In water/ethanol mixtures, ethanol transports through the membrane matrix, while water permeates through the polar pathways consisting of polar groups or ions and water molecules as well as through the membrane matrix. (C) 1995 John Wiley and Sons, Inc.
Keywords: ETHANOL WATER MIXTURES; SEPARATION; COEFFICIENTS; DIFFUSION; LIQUIDS